KAPANG ENDOFIT LAUT DARI TUMBUHAN PESISIR TERONG PUNGO (Solanum sp.) DAN POTENSINYA SEBAGAI ANTIBAKTERI - Nabila Ukhty (Universitas Teuku Umar, 2015)
Endophytic fungi is the one of the types microbes that lives in the plant tissue. The fungus can produce secondary metabolites potential as a source of antimicrobial and anticancer. The objectives of this study was to the exploration of new antibacterial compounds derived from marine endophytic fungi isolated from coastal plant terong pungo (Solanum sp.). Eight isolates of marine endophytic fungi with different morphology were collected. Endophytic fungus TPL2 was the selected isolate based on antagonism test. The growth curve showed the stationary phase of isolate TPL was on the 9th day to 12th day. Crude extract of endophytic fungi TPL2 showed the antibacterial activity against Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa with diameter of inhibition zone 4 mm, 6 mm, and 6 mm, respectively for 2 mg extract/well.